B27 Disruption of melatonin circadian rhythmicity in Huntington's disease (HD). (29th August 2012) - Kalliolia, E; Kalliolia, R; Silajdzic, E; Nambron, R; Hill, N; Hindmarsh, P; Bjorkqvist, M; Warner, T
Abstract : Background: Disruption of the sleep cycle is common in HD. Melatonin regulates sleep in relation to the light/dark cycle, orchestrated by the hypothalamus and suprachiasmatic nucleus. Degeneration in hypothalamic neurons of transgenic mouse models and humans with HD has been reported. One study suggested that the nocturnal rise in melatonin levels is delayed. Aims: To study the circadian rhythm of melatonin in a 24 h study of control, premanifest and stage II/III HD subjects. Methods: Control (n=15), premanifest (n=14) and stage II/III (n=13) participants were studied with hourly blood sampling over a standardised 24-h period with identical day/night cycle. Blood samples were taken from an intravenous cannula, immediately centrifuged and stored at −80°C. Melatonin levels were measured by a commercially available radio immuno assay. Estimates of regularity of hormonal pulsatility were undertaken using Fourier transformation. Results: Individual measures of 24 h melatonin levels showed disturbance in stage II/III HD subjects compared to controls. The main periodicity of pulsatility for melatonin started at 120 min in all groups, but the strength of pulsatility was significantly reduced in moderate and premanifest subjects. This reduction in strength was maintained in stage II/III HD throughout the range of periodicity. Conclusions: Melatonin circadian rhythms are disrupted in HD and correlate with disease severity providing an explanation for disrupted sleep. Further work is required to understand the underlying mechanism and its potential as an HD biomarker. This study supports melatonin treatment of HD sleep disturbance.